Study on the Performance of Electrothermal Shape Memory Alloy and Magnetorheological Combined Drive - Yang Xiong; Jin Huang; Ruizhi Shu (Jixie chuandong)
In order to overcome the disadvantage of small transfer torque in single magnetorheological drive， a combined drive method of electrothermal shape memory alloy（SMA） and magnetorheological is proposed， which can improve the transfer torque of drive device. Based on the thermal effect characteristics of shape memory alloy， the relationship between extrusion force and temperature of electrothermal SMA spring is established. Maxwell software is used to carry out finite element analysis of the magnetic field and obtain the distribution of the magnetic field intensity along the radius in the working gap of the disc under different currents. Based on the magnetorheological characteristic of magnetorheological fluids， the relationship between the torque transferred by magnetorheological fluids and the parameters such as magnetic field strength and radius is established. Based on the extrusion characteristics of SMA springs， the relationship between friction torque and extrusion force， radius and other parameters is established. The results show that， the friction torque produced by the extrusion force of the electrothermal shape memory alloy spring increases with the temperature increasing. The magnetic field increases with increasing radius. The combined transfer torque of the electrothermal shape memory alloy and magnetorheological（MR） is 53.8% higher than that of a single MR transmission.